2021
DOI: 10.1101/2021.01.05.423837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of Protein Interactome Networks with Congenital Heart Disease Variants Reveals Candidate Disease Genes

Abstract: SUMMARYCongenital heart disease (CHD) is present in 1% of live births, yet identification of causal mutations remains a challenge despite large-scale genomic sequencing efforts. We hypothesized that genetic determinants for CHDs may lie in protein interactomes of GATA4 and TBX5, two transcription factors that cause CHDs. Defining their interactomes in human cardiac progenitors via affinity purification-mass spectrometry and integrating results with genetic data from the Pediatric Cardiac Genomic Consortium rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…More than 250 proteins were identified as potential GATA4 interacting partners, including several previously reported GATA4 interactors and novel interactors. 54 Surprisingly, there were many significant interactions between GATA4 and RNA-binding proteins belonging to the spliceosome complex (eg, SNRPF [small nuclear ribonucleoprotein polypeptide F], SF3A1 [splicing factor 3a subunit 1], SF3A3 [splicing factor 3a subunit 3]), RNA splicing regulators (eg, HNRNPF [heterogeneous nuclear ribonucleoprotein F], HNRNPR [heterogeneous nuclear ribonucleoprotein R]), and mRNA processing regulators (eg, DHX15 [DEAH-box helicase 15], SRRT [serrate RNA effector molecule homolog]; Figure 1B). Coimmunoprecipitation analysis of the GATA4 interaction with RNA-binding proteins, for which there are high quality antibodies, confirmed that interaction with SF3A3, HNRNPH1 (heterogeneous nuclear ribonucleoprotein H1), and SF3A120 (splicing factor 3 subunit 1) can indeed occur, even in the presence of RNAse (Figure 1C; Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 250 proteins were identified as potential GATA4 interacting partners, including several previously reported GATA4 interactors and novel interactors. 54 Surprisingly, there were many significant interactions between GATA4 and RNA-binding proteins belonging to the spliceosome complex (eg, SNRPF [small nuclear ribonucleoprotein polypeptide F], SF3A1 [splicing factor 3a subunit 1], SF3A3 [splicing factor 3a subunit 3]), RNA splicing regulators (eg, HNRNPF [heterogeneous nuclear ribonucleoprotein F], HNRNPR [heterogeneous nuclear ribonucleoprotein R]), and mRNA processing regulators (eg, DHX15 [DEAH-box helicase 15], SRRT [serrate RNA effector molecule homolog]; Figure 1B). Coimmunoprecipitation analysis of the GATA4 interaction with RNA-binding proteins, for which there are high quality antibodies, confirmed that interaction with SF3A3, HNRNPH1 (heterogeneous nuclear ribonucleoprotein H1), and SF3A120 (splicing factor 3 subunit 1) can indeed occur, even in the presence of RNAse (Figure 1C; Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…As most transcription factors function in complexes to regulate gene expression, our recent work investigated GATA4's protein interactome by using an antibody to the endogenous GATA4 for affinity purification followed by mass spectrometry in human iPS-CPs treated with RNase and DNase in triplicates (Figure 1A). 54 Human GATA4-null iPS-CPs were used as the negative control for nonspecific interactions. More than 250 proteins were identified as potential GATA4 interacting partners, including several previously reported GATA4 interactors and novel interactors.…”
Section: Gata4 Interacts With Rna Splicing Proteins In Human Ips-cpsmentioning
confidence: 99%